Higher Education Evasion: an analysis of the Physics Degree Course- João Câmara Campus (2009-2019) at the Rio Grande do Norte Federal Institute of Education, Science and Technology in Brazil (Research, Society and Development, 2020)
This article analyzes the phenomenon of scholar class evasion regarding the Physics undergraduate course the period of 2009 to 2019 in the Federal Institute for Education, Science and Technology of the State of Rio Grande do Norte in the João Câmara Campus in Natal-Brazil. The methodology used was a qualitative and quantitative approach considering evasion rates status present in Educational Reports from 2009 to 2019, profiles of incoming, evaded and alumni students; aiming to understand the frequency of institutional abandonment. Data was also collected through a solicitation sent to the course coordinator of the referred campus aiming to gather information regarding evaded student’s data available through the Academic Campus Office, in the Unified Public Administration System (Education module), statistics present in Education Indicators, the Institute´s Strategic Plan for Permanence and Success (2016-2018). The research was based on theoretical landmarks present in the works of Gaioso (2005), Baggi and Lopes (2011), Marques (2014), Santos and Silva (2011). Results reveal that student evasion is high in the Physics Degree Course in the João Câmara Campus reaching 76,7% of students from the class of 2013.  In addition to this, results enabled to draw a profile of the students regarding their course entry, their trajectory, as well as to raise reflections on the factors of this Brazilian institutional and educational problems, which are extremely important for the understanding the student evasion phenomenon in the realm of academic Education. The research output also enables to monitor indicators related to academic higher education.